Evaluation of Restaurant Taxpayer Compliance in Surabaya City Based on the SIMPADA Tax Reporting Ratio - Husnul Khotimah; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study evaluates restaurant taxpayer compliance in Surabaya based on the tax reporting ratio through the SIMPADA system (Regional Tax Information System). The research applies a descriptive quantitative method using secondary data obtained from the Regional Revenue Agency of Surabaya for the period 2023–2025. The purpose of this study is to assess the effectiveness of tax administration and monitoring efforts in improving compliance among restaurant taxpayers. The findings show that the restaurant tax reporting ratio experienced a gradual increase, rising from 60.33% in 2023 to 61.08% in 2025. This upward trend indicates a positive development in taxpayer compliance over the observed period. The implementation of SIMPADA, supported by real-time monitoring systems, contributes positively to compliance by simplifying tax reporting and payment procedures, improving administrative efficiency, and increasing transparency in tax management. Nevertheless, despite the improvement achieved, the effectiveness level remains below the expected target standard of 75%. Therefore, restaurant taxpayer compliance is still categorized as moderately effective. These results suggest that further optimization of the system, strengthened supervision mechanisms, and continuous taxpayer education programs are necessary to enhance compliance levels and support the achievement of local tax revenue targets more effectively and sustainably.